THE INFLUENCE OF COMPETENCE AND KNOWLEDGE MANAGEMENT ON PERFORMANCE - Hanum, Nikmah; Munandar, Jono Mintarto; Purwono, Joko (Universitas Brawijaya, Indonesia, 2020)
This study aims to examine and analyze the effect of competence and knowledge management on performance (a case study of BAPETEN employees). Respondents in this study were BAPETEN employees, totaling 490 respondents. Data were analyzed using Structural Equation Modeling (SEM) Amos with Amos software version 24. The results of this study found that competence and knowledge management affect positively and significantly on performance. And also gender as a moderating variable does not have a significant effect on employee performance or competence, due to the absence of a distinction between male and female genders. So it is expected that further researchers can expand the variables in improving performance in the company.